Pengaruh Pemberian Pembiayaan Muràbahah Terhadap Pemberdayaan Usaha Kecil: Studi Kasus di Baitul Mall Wa Tamwil (BMT) Maunah Kabupaten Tegal. - M.Masrukhan; Setya Pramono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Empowerment is basically a process that is run with the full awareness and preparation of the parties to increase the capacity and capability of the community in developing and helping themselves to the good state. Target awareness here is a small business, because most of them can not empower their business due to the difficulty of obtaining additional capital. BMT Maunah Tegal is one of the institutions supporting economic activity is shown to support the community and small businesses by presenting a variety of financing, one of which is murabahah. The purpose of this study was to describe the Murabaha financing and small business pemberdyaan performed at Baitul Mall wa Tamwil Maunah Tegal and determine the effect of Murabaha financing to small business empowerment. The method used in this study is a quantitative method, technique of data collection through questionnaires addressed to the respondent customers Baitul Mall wa Tamwil Maunah Tegal, and to study the documentation. Samples from the Baitul Mall Customer wa Tamwil Maunah Tegal by 69 respondents. Based on the survey results revealed that with df = ttable n-2, 69-2 = 67 finished ttable test of df 67 is 67 = 2292. T say if the significant value of t <t table so that H0 is rejected and H1 is accepted, whereas if t count> t table then H1 is accepted and H0 is rejected, so it can be concluded that the value of t (4364) and ttable of attachment (2292) then t count> t table so that H1 is accepted and H0 is rejected, thus meaning that the granting murabaha financing has significant influence to empower small businesses.